Anatomy of packaging structures. (SendPoints Publishing Co., Ltd., 2019)
Structure is an essential element in packing design. Apart from introducing the basic types of packaging structure and basic knowledge, this book focuses on presenting excellent creative packaging works from around the world. Each project selected exemplifies a unique design concept, which is a well of inspiration for readers worldwide. The accompanying DVD contains 60 copyright free and 175 copyrighted templates of packaging structure.